Pulling Outward but Reacting Inward: Mechanically Induced Symmetry-Allowed Reactions of cis- and trans-Diester-Substituted Dichlorocyclopropanes - Wang, Zi; Kouznetsova, Tatiana B.; Craig, Stephen L. (Synlett, 2022)
The mechanically induced symmetry-allowed disrotatory ring openings of cis- and trans-gem-dichlorocyclopropane (gDCC) diesters are demonstrated through sonication and single-molecule force spectroscopy (SMFS) studies. In contrast to the previously reported symmetry-forbidden conrotatory ring opening of alkyl-tethered trans-gDCC, we show that the diester-tethered trans-gDCC primarily undergoes a symmetry-allowed disrotatory pathway even at the high forces (>2 nN) and short-time scales (ms or less) of sonication and SMFS experiments. The quantitative force-rate data obtained from SMFS data is consistent with computational models of transition-state geometry for the symmetry-allowed process, and activation lengths of 1.41 ± 0.02 Å and 1.08 ± 0.03 Å are inferred for the cis-gDCC diester and trans-gDCC diester, respectively. The strong mechanochemical coupling in the trans-gDCC is notable, given that the directionality of the applied force may appear initially to oppose the disrotatory motion associated with the reaction. The stereochemical perturbations of mechanical coupling created by the ester attachments reinforce the complexity that is possible in covalent polymer mechanochemistry and illustrate the breadth of reactivity outcomes that are available through judicious mechanophore design.
Keywords: Woodward–Hoffmann; polymer mechanochemistry; structure–activity; gem-dichlorocyclopropane diester; sonication and single-molecule force spectroscopy